Multi-omics analysis revealed the role of CYP1A2 in the induction of mechanical allodynia in type 1 diabetes - Chen, Hongjin; Liao, Chenlong; Yang, Xiaosheng; Zhou, Han; Wu, Yiwei; Sun, Qiuyang; Li, Shuo; Zhang, Wenchuan (Frontiers in Genetics, 2023)
Mechanical allodynia (MA) is one of the leading clinical symptoms of PDPN, which is a primary reason for nontraumatic amputations, foot ulceration, and gait abnormalities in patients with diabetes. However, the pathogenic mechanisms of MA have yet to be fully elucidated, and there is no effective treatment. This study aims to study the potential pathogenetic mechanisms of MA and to provide targets for the therapy of MA. A single intraperitoneal injection of STZ-induced type I diabetes in SD rats and the rats were divided into the control group, the diabetic group without MA, and the diabetic group with MA based on weekly behavioral assays. The differentially expressed lipids in the sciatic nerve of each group were detected using untargeted lipidomics, and the differentially expressed genes in the sciatic nerve of each group were detected by transcriptomics. The pathogenesis of MA was predicted by Integrated Analysis and validated by immunofluorescence staining and transmission electron microscopy. Untargeted lipidomics revealed that a more severe accumulation of lipids occurred in MA rats; our transcriptomics results suggested that differentially expressed genes in MA rats were primarily related to lipid droplets and myelin sheath. The integrated analysis results indicated that the downregulation of CYP1A2 expression was closely linked to lipid metabolism disorders. Immunofluorescence staining demonstrated that down-regulation of CYP1A2 expression occurred in MA rats, and transmission electron microscopy results showed that more severe lipid droplets accumulation and degeneration of the myelin sheath occurred in the MA rats. Our findings imply that the downregulation of CYP1A2 expression leads to disorders of lipid metabolism and further leads to lipid droplet accumulation and myelin sheath degeneration, ultimately leading to the development of MA. Our study contributed to promoting the understanding of the molecular mechanisms of MA and providing potential targets for the clinical treatment of MA.